2014
DOI: 10.1136/gutjnl-2014-307020
|View full text |Cite
|
Sign up to set email alerts
|

A pro-inflammatory role for Th22 cells inHelicobacter pylori-associated gastritis

Abstract: ObjectiveHelper T (Th) cell responses are critical for the pathogenesis of Helicobacter pylori-induced gastritis. Th22 cells represent a newly discovered Th cell subset, but their relevance to H. pylori-induced gastritis is unknown.DesignFlow cytometry, real-time PCR and ELISA analyses were performed to examine cell, protein and transcript levels in gastric samples from patients and mice infected with H. pylori. Gastric tissues from interleukin (IL)-22-deficient and wild-type (control) mice were also examined.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
111
3
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(127 citation statements)
references
References 32 publications
(38 reference statements)
7
111
3
1
Order By: Relevance
“…Moreover, we observed an increased expression of CXCL2 (macrophage inflammatory protein 1␣) during the vaccine-induced reduction of H. felis infection (Fig. 4D); this chemokine has recently been shown to be upregulated in the stomach mucosa of H. pylori-infected patients and responsible for the recruitment of CXCL2R ϩ myeloid suppressive cells in their stomach mucosa (54). We are currently evaluating whether the recruitment of inflammatory monocytes in the vaccine-induced reduction of Helicobacter infection is CXCL2R dependent.…”
Section: Gr1mentioning
confidence: 82%
“…Moreover, we observed an increased expression of CXCL2 (macrophage inflammatory protein 1␣) during the vaccine-induced reduction of H. felis infection (Fig. 4D); this chemokine has recently been shown to be upregulated in the stomach mucosa of H. pylori-infected patients and responsible for the recruitment of CXCL2R ϩ myeloid suppressive cells in their stomach mucosa (54). We are currently evaluating whether the recruitment of inflammatory monocytes in the vaccine-induced reduction of Helicobacter infection is CXCL2R dependent.…”
Section: Gr1mentioning
confidence: 82%
“…The hallmark of H pylori-induced inflammatory response in gastric mucosa is the CD4 + T immune cell's infiltration. 17 Besides, Treg cells also take part in the H pylori-associated gastritis. 18 CD4 + Th cells infiltrating the gastric mucosa could be Th1, Th17, Th22, regulatory T cell (Treg) subsets and so on.…”
Section: Discussionmentioning
confidence: 99%
“…17 Thus, we stimulated AGS cells with a WT or cagA knockout (ΔcagA) strain of H pylori and found that BHLHE40 mRNA and protein levels only increased following infection with the WT, but not ΔcagA strain ( Figure 3A and Supplementary Figure 4A). cagA is a major virulence factor of H pylori, which is injected into GECs via the type IV secretion system (T4SS).…”
Section: H Pylori Induces Bhlhe40 Expression In Gecs Via the Caga-ementioning
confidence: 99%
“…Moreover, previous studies have demonstrated that CD4 ϩ LTi cells express IL-22 (28,35), an important cytokine in eliciting an antimicrobial immune response and maintaining mucosal barrier integrity within the intestine (36,37), in an IL-23-dependent manner (28,37). We showed that IL-7R␣ blockade in C. rodentium-infected mice led to a significant decrease in IL-23 expression in the colon, which may in turn inhibit the production of IL-22 by CD4 ϩ LTi cells.…”
Section: Discussionmentioning
confidence: 99%